Pengaruh Model Pembelajaran Kooperatif tipe CIRC (Cooperative Integrated Reading and Composition) Menggunakan Komik Biologi Untuk Meningkatkan Minat Belajar Siswa Dalam Materi Pencemaran Lingkungan Pada Siswa Kelas VII-A SMPN 1 Beringin: (Application Of The CIRC Type Cooperative Learning Model (Cooperative integrated Reading and Composition) With Biological Comic Media To Improve Student’s Learning Interest In Biology Lessons On Environmental Pollution Materials In Class VII-SMPN 1 Beringin) - Agus Wahyuda; Ananda Putri Ananda Putri; Bella Villanda Bella Villanda; Widiya Tri Utami Widiya Tri Utami; Windari Ramdani Windari Ramdani (BIODIK, 2023)
The purpose of this study was ti increas student’s interest in learning biology for class VII A of SMPN 1 Beringin through the application of the CIRC type cooperative learning model with biological comic media on enviromental pollution material. This reasearch is a classroom action reasearch which takes place in 3 cycles. Each cycle consists of 4 basictages, namely planning, action, observation, and reflection. Collecting reasearch data using guestionnaires, observation sheets, and interviews. The validity of the data was measured by using a triangulation techniq, namely the triangulaton method.The data analysis tehnique used descriptive analysis technique. The The results of this study indicate that in the first cycle based on the observation sheet the average percentage of students' learning interest in the class was 57.53%, 65.12% in the second cycle (increased 7.59%), and 83.28% in the third cycle. (an increase of 18.16%). Meanwhile, based on the questionnaire, the average percentage of students' achievement in learning interest in the first cycle was 71.04%, 71.77% in the second cycle (an increase of 0.73%), 73.66% in the third cycle (an increase of 1.89%) . The results of student interviews can be concluded that students are happier and find it easier to learn biology lessons. Students are also interested in learning, students also feel that learning during action is an interesting activity. This research is the application of the CIRC learning model accompanied by biological comics media on Environmental Pollution material can increase student interest in learning in class VII A SMP Negeri 1 Banyan 1 school year 2022 / 2023. Key words: cooperative integrated reading and composition learning model, biological comics, student learning interest ABSTRAK Penelitian ini bertujuan untuk meningkatkan minat belajar biologi siswa kelas VII A SMP Negeri 1 Beringin menggunakan lingkungan eksfoliasi biologis untuk pencemar lingkungan dan model pembelajaran umum tipe CIRC. Penelitian ini merupakan penelitian perilaku klasik tiga siklus. Setiap siklus terdiri dari empat fase utama: perencanaan, pelaksanaan, pemantauan dan refleksi. Mengumpulkan data penelitian melalui kuesioner, daftar periksa dan wawancara. Validitas data diukur dengan triangulasi, yaitu triangulasi. Metodologi analisis data menggunakan metode analisis deskriptif. Setelah penelitian ini, minat siswa untuk kelas pada siklus 1 rata-rata adalah 57,53%, 65,12% (meningkat 7,59%) pada siklus 2 dan 83,28% berdasarkan tes kerja. siklus ketiga. (meningkat 18,16%). Selain itu, berdasarkan survei, rata-rata kemajuan belajar siswa pada siklus 1 adalah 71,04%, siklus 1 71,77% (meningkat 0,73%) dan siklus 2 73,66% (peningkatan 1,89%) pada siklus 3. Dari wawancara siswa Anda dapat menyimpulkan bahwa siswa lebih bahagia dan belajar pelajaran biologi lebih mudah. Dapat disimpulan penerapan model pembelajaran CIRC pada bahan pencemar lingkungan dengan menggunakan komik biologi dapat meningkatkan minat belajar siswa di SMP Negeri 1 Beringin Kelas VII-A tahun pelajaran 2022/2023. Kata kunci: model pembelajaran CIRC, komik biologi, minat belajar siswa